INHIBITORY EFFECTS OF ASPHALTENES AND RESINOUS COMPONENTS IN CRUDE OIL PROCESSING AND METHODS FOR THEIR NEUTRALIZATION. - Raxmonqulova Marjona Baxtiyorovna; Arzimurodova Xonbuvi Jamol qizi; Kosimova Xurshida Rajabboyovna (Research Focus International Scientific Journal, 2025)
This article investigates the inhibitory effects of asphaltenes and resinous components on various stages of crude oil processing, including distillation, catalytic cracking, and pipeline transportation. These high-molecular-weight, polar compounds tend to aggregate, leading to increased viscosity, equipment fouling, catalyst deactivation, and flow assurance challenges. Their chemical complexity and strong intermolecular interactions make them particularly resistant to conventional separation techniques. The article reviews state-of-the-art neutralization strategies, including chemical dispersants, surface-active agents, and nanomaterial-based solutions. Experimental insights into additive performance, interaction kinetics, and process optimization are presented to evaluate their practical applicability.